ANALISIS PERUBAHAN GARIS PANTAI AKIBAT PENGARUH PEMASANGAN GROPOZAG (Studi Kasus Pantai Neuhen, Aceh Besar) - Sofyan Andre; Eldina Fatimah; Syamsidik Syamsidik (Teras Jurnal : Jurnal Teknik Sipil, 2021)
Abstract At the present time, a lot of researchs and treatments have been carried out by experts to minimize the bad effects due to erosion and sedimentation, including the application of groin. Beach structure of the groyne generally used on the Indonesia beaches is groin solid model (impermeable) in which no water can pass the groin. The various types, configuration, material, and height of groin have been applied in Aceh. One of the types is porous zig-zag type groin (gropozag). This type had been tested both as physical model in the laboratory and numerical model. However, the performance application in the field had been rarely carried out. This paper aims to determine the effect of the gropozag application on the coastline changes in the Neuheun Beach. The groin was made of cubes arranged in a zigzag pattern. The size of a unit cube was 1m x 1m x1m with several holes on either side. The upper side was open and the bottom side was completely closed without any holes. Several cube units were assembled into a single groyne series and placed perpendicular to the coast. The observation carried out was without gropozag condition year 2017 and after gropozag installation tear 2019. Output of the research showed that the Gropozag application affected the coastline changes in the left and right area of the Gropozag. The erosion carried out in the left side of the gropozag which was affected by the waves from northeast was higher than the right side of the gropozag. Keywords: coastline change, sedimentation, erosion, groin, gropozag